A capability model for public administration interoperability. Issue 8 (13th September 2020) - Almeida Prado Cestari, José Marcelo; Loures, Eduardo de Freitas Rocha; Santos, Eduardo Alves Portela; Panetto, Hervé
ABSTRACT: Interoperability is a critical factor for entities that operate in collaborative/cooperative environments. Performing an interoperability diagnosis based on a reference model allows an organization to know its strengths and prioritize actions, improving performance and maturity. In public administration, this issue is more emphasized due to national or international policies. This paper proposes a Public Administration Interoperability Capability Model (PAICM) that describes intervals of expected results regarding the capability degree of certain attributes. The PAICM was applied to a government information technology agency, enabling the identification of the different barriers affecting organizational performance and a stratified analysis of the potential interoperability.